The effectiveness of the localized model of schema therapy on changing the schema of therapists - Mandana Shaeban; mehrangiz Peyvastegar; zohreh khosravi (مجله علوم روانشناختی, 2021)
Background: Psychotherapy for therapists increases emotional development and improves interpersonal skills and empathy, as well as self-awareness in understanding individual problems, conflicts, and values; Accordingly, the main question of the research is whether the native model of schema can affect the performance of therapists. Aims: The aim of this study was to determine the effectiveness of the localized model of therapeutic design on changing the schemas of therapists. Method: Method was quasi-experimental with pre-test, post-test and a three-month follow-up, Out of 55 therapists of Ofogh Salamat, Hamraz, Savalan and Ordibehesht Counseling Centers in District 5 of Tehran, 16 therapists were selected using sampling and were randomly assigned to two experimental groups (8 people) and witnesses (8 people). Both groups responded to the Young Response Questionnaire (1994) in three stages: pretest, posttest, and follow-up. The experimental group participated in 10 90-minute sessions in the treatment interventions of the localization of the schema therapy protocol (Farell & Shaw, 2018) for the therapists, and the control group did not receive any intervention. The data were analyzed using repeated measures variance of analysis Results: Variation analysis of repeated measurements showed that the two groups were significantly different in reducing other areas of severity and earache (P< 0/05); The results also show that the scores of other areas (cutting and rejection, self-regulation and dysfunction) of the subjects in the experimental group decreased compared to the control group after the intervention, but this decrease was not significant (P< 0/05). Conclusions: The localized model of schema therapy modified schemas in other areas of attention and eloquence; Therefore, it can be expected that the localized model of treatment plan will help the therapist to recognize his unhealthy mentalities.